Use of light-emitting diodes on the morpho-anatomical characteristics of Corymbia citriodora seedlings - de Azevedo, Gabrieli Cristina Vitalli; Nardini, Claiton; Pretto, Matheus Milani [UNESP]; de Cristo, João Antonio; dos Santos Silva, Erick; Eloy, Elder; Caron, Braulio Otomar; Schmidt, Denise (Instituto de Pesquisa e Estudos Florestais (IPEF), 2022)
With the increase in Corymbia citriodora cultivation in Brazil, it is crucial to evaluate its characteristics in different environments of seedling production, given the different acclimatization strategies under the prevailing environmental conditions in its cultivation. The objective of this study was to evaluate distinct spectral qualities of LEDs lamps in morpho-anatomical characteristics in Corymbia citriodora seedlings. The work was conducted from August 2018 to January 2019, in a growth room. The experimental design used was completely randomized, where the treatments were composed of four spectral qualities of light from white, red (660 nm), blue (450 nm) and blue + red (40% + 60%) LED lamps, with light intensity of 72 µmol m-2 s-1 each bench. For Corymbia citriodora, the different spectral qualities affected characteristics such as leaf blade thickness, leaf area, dry matter, stomatal density, decreased chlorophyll b and total chlorophyll content under red LED and caused lower epidermis thickness under blue LED cultivation. The use of white spectral quality is the most appropriate and favors the dispatch of seedlings at 102 days after emergence, both in the parameters evaluated for leaf area index and for dry matter.
Uso de diodos emissores de luz sobre as características morfoanatômicas em mudas de Corymbia citriodora
Keywords: Leaf area index; LEDs; Lemon-scented gum; Light